PENGARUH RELIGIUSITAS, FASILITAS LAYANAN, LITERASI KEUANGAN DAN BAGI HASIL TERHADAP MINAT MAHASISWA UNTUK MENABUNG DI BANK SYARIAH - Livia Deni Zakaria; Afifudin Afifudin; M. Cholid Mawardi (Universitas Islam Malang, 2020)
ABSTRACT This research was conducted to determine the influence of Religious, Service Facilities, Financial Literacy and Profit Sharing on Student Interest in Saving in Islamic Banks. In this study, researchers took a sample of 93 respondents from active students of the economics faculty, majoring in accounting, class 2016 and 2017 who had taken the Sharia Accounting course. The analysis method used is multiple linear regression. Based on the test results, it can be concluded that simultaneously religious variables, service facilities, financial literacy and profit sharing have a significant influence on students' interest in saving at Islamic banks. Partially, the variables of religiosity, service facilities and financial literacy have no effect on students' interest in saving at Islamic banks. Meanwhile, the profit sharing variable has an influence on students' interest in saving at Islamic banks.Keywords: Religious, Service Facilities, Financial Literacy, Profit Sharing and Student Interest in Saving at Islamic Banks.